Exploring Lawyer Misconduct: An Examination of the Self-Regulation Process. Issue 5 (3rd May 2016) - Piquero, Nicole Leeper; Meitl, Michele Bisaccia; Brank, Eve M.; Woolard, Jennifer L.; Lanza-Kaduce, Lonn; Piquero, Alex R.
ABSTRACT: Although white-collar professionals are often held in high esteem, sometimes persons in privileged positions engage in misconduct. Unfortunately, very little is known about the correlates associated with professional misconduct and even less is known about the sanctioning process among lawyers who are licensed by state bar associations and therefore subject to the bar rules regulating their professional conduct. We examine 213 complaints filed in one fiscal year with the Florida Bar, alleging attorney misconduct and evaluate the factors that influence whether the complaint continued through, or was discarded at, each stage of the self-regulated grievance process. Using selection models that examine both the staff's decision to send a case forward to the grievance committee as well as the grievance committee's recommendation about sanctioning the lawyer, results show that both legal and extra-legal variables are related to these two processes.